O método da malha quadriculada como recurso pedagógico para a inclusão de uma aluna com deficiência visual monocular no ensino da multiplicação: um estudo de caso - SILVA, Nayara Damasceno da (2024)
The present study aimed to present the checkerboard mesh method, used by a mathematics teacher as an effective pedagogical resource for the multiplication teaching-learning process, applied in the classroom to a student with monocular visual impairment, with the intention to make the teaching-learning of multiplication accessible to students, aiming to include them in mathematics classes. This research was carried out in a regular public school located in the city of Salinópolis-PA, it is qualitative in nature and had a case study methodology, where data collection instruments were used such as participant observation, interviews, questionnaires and verification of the content applied in the classroom, through which records of the research subjects were made. The results obtained were satisfactory, as using this method, the mathematics teacher was able to explain multiplication concepts in order to promote the inclusion of her student in mathematics classes, which allowed the student to improve her skills such as: autonomy, creativity, reflection, interpretation and socialization in the school environment.